The efficacy of peripheral nerve block on postoperative catheter-related bladder discomfort in males: A systematic review and meta-analysis - Bao, Xingjun; Liu, Ming; Li, Jie; Yao, Huibao; Liu, Hongquan; Tang, Gonglin; Wang, Xiaofeng; Zhou, Zhongbao; Wu, Jitao; Cui, Yuanshan (Frontiers in Surgery, 2023)
Objective To determine the efficacy of peripheral nerve block (PNB) in preventing postoperative catheter-related bladder discomfort (CRBD). Methods Up to July 1, 2022, the PubMed, Embase and Cochrane Central Register of Controlled Trials databases were searched, and all articles that met the PICOS (Patient, Intervention, Comparator, Outcome, Study design) criteria were enrolled. The included trials were evaluated using the Cochrane Collaboration's tool. Patients in the block group received bilateral PNB, while those in the non-block group did not need any additional procedure or simply achieved “sham block”. CRBD was quantified using the visual analog scale (VAS) score, which was questioned and recorded at 0–1 h, 1–2 h, 4–8 h, 8–12 h and 12–24 h intervals. The incidences of CRBD, moderate to severe CRBD and postoperative nausea and vomiting (PONV) were meta-analysed. Results Six trials with a total of 544 patients were considered. First, the block group had a lower incidence of CRBD than the non-block group at 0–1 h (OR 0.22; 95% CI, 0.18–0.08; P < 0.0001), 1–2 h (OR 0.14; 95% CI, 0.08–0.26; P < 0.00001), 4–8 h (OR 0.27; 95% CI, 0.13 to 0.58; P < 0.0008) and 8–12 h (OR 0.51; 95% CI, 0.30 to 0.87; P = 0.01). Second, the block group showed a lower incidence of moderate to severe CRBD than the non-block group at 0–1 h, 1–2 h and 4–8 h, and the ORs were 0.12 (95% CI, 0.03 to 0.49; P = 0.003), 0.17 (95% CI, 0.08 to 0.37; P < 0.00001) and 0.29 (95% CI, 0.15 to 0.55; P = 0.0002),respectively. Finally, the block group was significantly associated with a decreased incidence of PONV (OR, 0.14; 95% CI, 0.05 to 0.39; P = 0.0002). Conclusion This meta-analysis suggested that PNB markedly reduced the incidence and severity of early postoperative CRBD and decreased the occurrence of PONV.